ANALISIS KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi pada Biro Keuangan Kementrian Agraria dan Tata Ruang) - Donna Pembriastuti (2019)
The purpose of this study was to analyze the effect of competence, leadership style, work culture and work environment on employee job satisfaction at the Finance Bureau at the Ministry of Agriculture and Spatial Planning. Next to analyze the effect of employee job satisfaction on employee performance at the Finance Bureau at the Ministry of Agriculture and Spatial Planning. The research method used in this study is a quantitative method with a causality approach. The population in this study were all employees of the Ministry of Agrarian and Spatial Finance Bureau totaling 77 employees. Determination of the number of samples carried out using the probability sampling method with sampling techniques carried out by saturation or census sampling where the sampling technique is done when all members of the population are used as samples. Then the number of samples in this study were 77 respondents who were employees of the Finance Bureau of the Ministry of Agriculture and Spatial Planning. Data analysis method used in this study uses Partial Least Square (PLS). The results in this study indicate that partially competence, leadership style, work culture, and work environment are proven to have an influence on employee job satisfaction at the Finance Bureau at the Ministry of Agrarian Affairs and Spatial Planning. While employee job satisfaction is proven to have an influence on employee performance at the Finance Bureau in the Ministry of Agrarian Affairs and Spatial Planning